2005
DOI: 10.1128/jvi.79.5.3217-3222.2005
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus/Human Herpesvirus 8 RTA Reactivates Murine Gammaherpesvirus 68 from Latency

Abstract: Murine gammaherpesvirus 68 (MHV-68), Kaposi's sarcoma-associated herpesvirus (HHV-8), and EpsteinBarr virus (EBV) are all members of the gammaherpesvirus family, characterized by their ability to establish latency in lymphocytes. The RTA protein, conserved in all gammaherpesviruses, is known to play a critical role in reactivation from latency. Here we report that HHV-8 RTA, not EBV RTA, was able to induce MHV-68 lytic viral proteins and DNA replication and processing and produce viable MHV-68 virions from lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Real-time PCR using primers against MHV-68 M1 was performed (18). While pORF49 null transfection alone evidenced highly attenuated virus replication, cotransfection of pFLAG-ORF49 significantly increased the viral genome copy number of pORF49 null to a level comparable to that of the wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Real-time PCR using primers against MHV-68 M1 was performed (18). While pORF49 null transfection alone evidenced highly attenuated virus replication, cotransfection of pFLAG-ORF49 significantly increased the viral genome copy number of pORF49 null to a level comparable to that of the wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Total genomic DNAs were extracted from the cells and digested with DpnI to remove the transfected BAC DNA. Real-time PCR using primers against MHV-68 M1 was performed to quantitate viral DNA, as described previously (18). (B) Increased viral gene expressions of the ORF49 null virus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pFLAG-CMV2 (Sigma)-based wild-type (WT) MHV-68 RTA mammalian expression vector was described previously (31). The alanine substitutions in the RTA coding region were introduced by two-step PCR.…”
Section: Methodsmentioning
confidence: 99%
“…7). Our previous studies have demonstrated that the transcomplementation assay is efficient for recapitulating the phenotypes of mutant viruses (2,17,31,39,40). For the transactivation assay, the cells were transfected with MHV-68 RTA promoter reporter plasmid (1-kb sequence upstream of the MHV-68 RTA exon 1 translational initiation codon driving a firefly luciferase gene) and vector plasmid or wild-type or mutant RTA expression plasmids.…”
Section: Generation Of the 15-bp Insertion Mutant Rta Locus Librarymentioning
confidence: 99%